Numerical Methodology for Enhancing Heat Transfer in a Channel with Arc-Vane Baffles - Thapmanee, Piphatpong; Phila, Arnut; Wongcharee, Khwanchit; Maruyama, Naoki; Hirota, Masafumi; Chuwattanakul, Varesa; Eiamsa-ard, Smith (My University, 2025)
This study numerically investigates flow and heat transfer in a channel with arc-vane baffles at various radius-to-channel high ratios (r/H = 0.125, 0.25, 0.375, and 0.5) for Reynolds numbers between 6000 and 24,000, focusing on solar air-heater applications. The calculations utilize the finite volume method, and the SIMPLE algorithm is executed with the QUICK scheme. For the analysis of turbulent flow, the finite volume method with the Renormalization Group (RNG) k-ε turbulence model was used. The results show that arc-vane baffles create double vortices along the axial direction, promoting flow reattachment on the heated surface and enhancing heat transfer. Baffles with smaller r/H ratios strengthen flow reattachment, reduce dead zones, and improve fluid contact with the heat transfer surface. The baffles with the smallest r/H ratio achieve a Nusselt number ratio (Nu/Nus) of 4.91 at Re = 6000. As r/H increases, the friction factor (f) and friction factor ratio (f/fs) rise due to increased baffle curvature and surface area. The highest thermal performance factor (TPF) of 2.28 occurs at r/H = 0.125 and Re = 6000, reflecting an optimal balance of heat transfer and friction losses. Arc-vane baffles with a r/H ratio of 0.125 yield a TPF exceeding unity, indicating potential energy savings. These findings provide valuable insights for optimizing baffle designs to enhance thermal performance in practical applications.
Keywords: arc-vane baffle; channel; heat transfer enhancement; solar air heater; vortex